A novel semantic medical access monitoring system for e-health applications using internet of medical things - Bommasani, Lahari Vyshnavi; Babu, Erukala Suresh; Aluri, Sasank (International Journal of Engineering and Technology, 2017)
Internet of things can connect various smart devices together by using Internet. It also provides data interoperability methods for application purpose. We have proposed an IOT -based framework for emergency medical services to show how to collect, integrate, and interoperate IOT data flexibly and also to support medical emergency services. By the development of IOT technologies, we can use medical sensors to monitor patientâ€™s health even without the presence of doctor. We came up with a outline of Semantic Medical Monitoring Framework with the help of cloud based IOT techniques. IOT health sensors will accept the massive data from the patient for every 6sec. All these data will be stored in the cloud and medical data will be connected to a medical rule engine through a web service called â€œTHINK SPEAKâ€. It also permits supervision of patient by remote centers and personal platforms such as mobiles, tablets. Regarding Hardware it provides a gateway and personal clinical devices used for continuous wireless transmission of monitored data of the patient.